2015
DOI: 10.5539/ijef.v7n7p229
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Corporate Dividends Policy: Evidence from an Emerging Economy

Abstract: The objective of this study is to establish the relationship between dividend policy and the attributes of non-financial companies listed on Abu Dhabi Securities Exchange (ADX). The companies comprise manufacturing, services, food staples, energy, telecommunications and property and real estate. To achieve this objective, panel data for the period between 2010 and 2012 were collected from the listed companies' annual reports published on ADX website. The result of the analysis revealed that dividend policy is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0
10

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 57 publications
3
28
0
10
Order By: Relevance
“…These results are different from the predictions that company size, as measured by market capitalization, negatively affects dividend policy. However, these findings are in line with Manneh and Naser (2015) that firm size has a positive and significant effect on the dividend payment ratio.…”
Section: Descriptive Statisticssupporting
confidence: 84%
See 2 more Smart Citations
“…These results are different from the predictions that company size, as measured by market capitalization, negatively affects dividend policy. However, these findings are in line with Manneh and Naser (2015) that firm size has a positive and significant effect on the dividend payment ratio.…”
Section: Descriptive Statisticssupporting
confidence: 84%
“…Managerial ownership might also affect dividend payout policy. Companies with high growth tend to retain their profits to fund their investments (Manneh & Naser, 2015). The thing is that the higher the growth of the company, the greater is the fund needed to support the company's growth, but consequently, the paid dividend will be lower.…”
Section: Business Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Manneh and Naser (2015) examined the relationship between dividend policy and the attributes of non-financial companies listed on Abu Dhabi Securities Exchange (ADX) over the period 2010-2012. The result of the analysis revealed that dividend policy is positively and significantly associated with corporate profitability, risk, free cash flows, size, majority shareholders and industry.…”
Section: Empirical Evidence On the Dividend Theoriesmentioning
confidence: 99%
“…The study revealed that a situation with the payment of dividends in the corporate sector in Ukraine is quite indistinctive for more developed and emerging stock markets where payment of dividends is not an exclusion [Baker and Kapoor 2015, Forti and Schiozer 2015, Kadioglu et al 2015, Manneh and Naser 2015, Yaseen et al 2015 Is it possible to explain the mass abandonment of dividends payment with the help of modern theories of dividend policy, that were considered in the LITERATURE REVIEW section?.…”
Section: Discussionmentioning
confidence: 99%